WTO Agriculture Negotiations: Implications for the Global South - Jennifer Clapp (Third World Quarterly, 2006)
The Doha 'Development' Round of trade negotiations at the WTO  has featured agricultural trade liberalisation as one of its key aims. But  developing countries were frustrated with both the process and the content of the  agricultural agreement negotiations early on in the round. This prompted these  countries, through a number of developing country groupings such as the G-20  and others, to call for changes in the talks to ensure that developing country  voices and concerns were heard. Although developing countries were in many  ways successful in registering their concerns in the latter half of the  negotiations, and have maintained a fairly high degree of cohesion across the  Global South, it remains unclear whether this cohesion will last as the uneven  impacts of agricultural trade liberalisation become apparent.